Long-term radiobiological effects in rats after exposure of 131I in utero - V. V. Talko; A. I. Lypska; I. P. Drozd; Ye. M. Prokhorova; O. A. Boyko; O. S. Vatlitsova; S. M. Aliokhina; O. Ya. Pleskach; O. M. Lytvynets (Ядерна фізика та енергетика)
Remote radiobiological effects in male rats prenatally exposed by 131I in different periods of gestation were studied. It was established that the negative effects of irradiation of 131I in utero in the distant period are manifested by disorders of the functioning of the pituitary-thyroid link of endocrine regulation, pro-antioxidant equilibrium, changes in the lipid-lipoprotein spectrum of blood serum. As a result of irradiation of 131I in utero throughout the period of gestation, discoordination in the functioning of the pituitary-thyroid link of endocrine regulation, a violation of the pro-antioxidant balance by increasing the intensity of lipoperoxidation processes and the activity reducing of enzymes of antioxidant defense, the atherogenic orientation of changes in the lipid-lipoprotein spectrum was established. As a result of irradiation by 131I in utero during the third trimester of gestation, the development of hypothyroidism, changes in pro-antioxidant balance due to the activation of antioxidant defense, and the reduction of the concentration of the main classes of lipids have been established.